2009
DOI: 10.1111/j.1440-1843.2009.01666.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of acute respiratory deterioration in pulmonary fibrosis associated with lung cancer following anti‐cancer therapy

Abstract: Patients with lung cancer who have pre-existing PF should be carefully managed because of their high risk for developing acute respiratory deterioration after anti-cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 25 publications
2
34
2
Order By: Relevance
“…Further, pre-existing ILD was found to be a risk factor of pneumonitis. Similarly, previous studies reported that approximately 20% of patients with pre-existing ILD developed pneumonitis, and that pre-existing ILD is the most significant risk factor [3, 2024]. Based on these findings, pneumonitis seems to be a relatively common event in patients with advanced NSCLC.…”
Section: Discussionmentioning
confidence: 57%
“…Further, pre-existing ILD was found to be a risk factor of pneumonitis. Similarly, previous studies reported that approximately 20% of patients with pre-existing ILD developed pneumonitis, and that pre-existing ILD is the most significant risk factor [3, 2024]. Based on these findings, pneumonitis seems to be a relatively common event in patients with advanced NSCLC.…”
Section: Discussionmentioning
confidence: 57%
“…Since available therapeutic options for AE are scarce and no established standard of care exists at present, this clinical condition is associated with an extremely poor prognosis [9][10][11]. In patients with lung cancer and preexisting IP, AE frequently occurs during anticancer treatments, including chemotherapy [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The median survival was 3.5 years for patients with an oncogenic driver and genotype-directed therapy, compared with 2.4 years for those with any oncogenic driver(s) who did not receive genotype-directed therapy. By contrast, patients with severe complications, such as ILD, are excluded from a number of clinical trials, as pre-existing ILD is a risk factor for the NSCLC therapy related to ILD (10,11).…”
Section: Introductionmentioning
confidence: 99%